2008
DOI: 10.2527/jas.2008-1032
|View full text |Cite
|
Sign up to set email alerts
|

Effects of duration of zilpaterol hydrochloride feeding and days on the finishing diet on feedlot cattle performance and carcass traits1

Abstract: British and British x Continental steers (n = 560; initial BW = 339.4 +/- 1.76 kg) were used in a serial slaughter study with a completely random design to evaluate effects of zilpaterol hydrochloride (ZH; 8.33 mg/kg of dietary DM basis) on performance and carcass characteristics. Treatments were arranged in a 4 x 4 factorial (112 pens; 7 pens/treatment; 5 steers/pen) and included duration of ZH feeding (0, 20, 30, or 40 d before slaughter plus a 3-d ZH withdrawal period) and days on feed (DOF) before slaughte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

29
83
6
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 96 publications
(125 citation statements)
references
References 9 publications
29
83
6
3
Order By: Relevance
“…The relatively larger differences between C and Z for carcass gain relative to live weight gain correspond with the increase (P , 0.05) in dressing percentage of up to 1.3 for Z30 and Z40. Similar improvements were reported by Neill et al (2009) for cull cows, whereas up to 2 increased dressing percentage were reported for young animals by Avendañ o-Reyes et al (2006), Vasconcelos et al (2008) and Montgomery et al (2009). No significant difference in carcass weight was recorded in this study, but this could have been due to large variation within cow groups combined with numerical differences in weight at the start of Neill et al (2009), zilpaterol had no significant effect on fat thickness measurements or chemical fat content of the three rib cut of cull cows that concur with fat measurements in this study.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…The relatively larger differences between C and Z for carcass gain relative to live weight gain correspond with the increase (P , 0.05) in dressing percentage of up to 1.3 for Z30 and Z40. Similar improvements were reported by Neill et al (2009) for cull cows, whereas up to 2 increased dressing percentage were reported for young animals by Avendañ o-Reyes et al (2006), Vasconcelos et al (2008) and Montgomery et al (2009). No significant difference in carcass weight was recorded in this study, but this could have been due to large variation within cow groups combined with numerical differences in weight at the start of Neill et al (2009), zilpaterol had no significant effect on fat thickness measurements or chemical fat content of the three rib cut of cull cows that concur with fat measurements in this study.…”
Section: Discussionsupporting
confidence: 83%
“…In addition, limiting the zilpaterol to the last 30 days seemed to give the best results compared with 20 days and did not differ significantly from 40 days of supplementation. Improvement in rate of body weight gain (average daily gain (ADG); P.0.05; , 9%) and efficiency of gain (feed conversion ratio (FCR); P , 0.05; , 14%) of cull cows in this study was consistent with improvements in ADG (12.5% to 36%) and FCR (15.3% to 21%) of younger animals fed zilpaterol (Avendañ o- Reyes et al, 2006;Vasconcelos et al, 2008;Montgomery et al, 2009). When measured on a carcass basis, ADG and FCR of 18% and 23%, respectively, between C and Z30 were recorded.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations